Marketing strategies of F-Commerce Business, Shop-Up during the Covid-19 - Inti, Mehnaz Farzin (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.